Investigation of olive mill wastewaters treatment by immobilized microalgae - Martins, Bruna da Silva (2018)
﻿﻿Olive mill wastewater (OMW) is characterized by minimum levels of nitrogen compounds and low pH, as well as very high organic load, due to high levels of phenolic compounds and sugars [1,2]. OMW direct disposal may pollute both, land and aquatic environments [1], therefore is one of the most serious environmental problems in producers countries. Although the two-phase method is a most innovative technique, in Portugal still exist the three-phase process. In this work, immobilized microalgae were tested to treat OMW, in order to reduce phyto-toxicity. From our knowledge it appears that OMW treatment methods with microalgae is a pioneering technique.